2007
DOI: 10.1111/j.1365-2672.2007.03351.x
|View full text |Cite
|
Sign up to set email alerts
|

Viable but non-culturableListeria monocytogeneson parsley leaves and absence of recovery to a culturable state

Abstract: Aims:  To investigate the presence of viable but non‐culturable Listeria monocytogenes during survival on parsley leaves under low relative humidity (RH) and to evaluate the ability of L. monocytogenes to recover from VBNC to culturable state under satured humidity. Methods and Results:  Under low RH (47–69%) on parsley leaves, the initial number of L. monocytogenes populations counted on non selective media (109 L. monocytogenes per leaf on TSA) was reduced by 6 log10 scales in 15 days, whereas number of viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 46 publications
(78 reference statements)
3
52
0
Order By: Relevance
“…Viability was reduced by a 2 log 10 scale within the first 2 days and then reached a level that remained stable until the end of experiment (12 days postinoculation) for both strains. Similar results were reported by Dreux et al (15) when parsley plants inoculated with 10 9 culturable L. monocytogenes bacteria per leaf were exposed to low relative humidity (47 to 69%), and the viable population detected decreased based on the same biphasic pattern (15). In a more stressful challenge (8°C) the entire E. coli population evolved toward a VBNC state, but the time required to induce the VBNC response was different for selected strains.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Viability was reduced by a 2 log 10 scale within the first 2 days and then reached a level that remained stable until the end of experiment (12 days postinoculation) for both strains. Similar results were reported by Dreux et al (15) when parsley plants inoculated with 10 9 culturable L. monocytogenes bacteria per leaf were exposed to low relative humidity (47 to 69%), and the viable population detected decreased based on the same biphasic pattern (15). In a more stressful challenge (8°C) the entire E. coli population evolved toward a VBNC state, but the time required to induce the VBNC response was different for selected strains.…”
Section: Discussionsupporting
confidence: 74%
“…Recently, Brandl et al (7,8) demonstrated that E. coli O157:H7 and Salmonella enterica can multiply on the leaf surface at incubation temperatures of between 16 and 30°C (7,8). Dreux et al (15) studied the fate of Listeria monocytogenes on parsley leaves under high and low relative humidity (47 to 69%) and reported induction of the VBNC state due to the stress caused by changes in water availability (15). In our study, exposure of E. coli O157:H7 to low temperatures of 8°C and 16°C on the surface of a coldseason plant was considered comparable for natural conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations